2009
DOI: 10.1007/s11431-009-0153-x
|View full text |Cite
|
Sign up to set email alerts
|

Constructal multidisciplinary optimization of electromagnet based on entransy dissipation minimization

Abstract: Based on entransy dissipation, the mean temperature difference of solenoid (electromagnet) with high thermal conductivity material inserted is deduced, which can be taken as the fundament for heat transfer optimization using the extremum principle of entransy dissipation. Then, the electromagnet working at steady state (constant magnetic field, constant heat generating rate per unit volume) is optimized for entransy dissipation minimization (i.e. mean temperature difference minimization) with and without volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 25 publications
(30 reference statements)
0
19
0
2
Order By: Relevance
“…(i) Constructal entransy dissipation rate minimization with fixed magnetic field [159]. Based on the concept of entransy dissipation, the expression of the mean temperature difference with high thermal conductivity material inserted in the solenoid (electromagnet) was deduced.…”
Section: Multi-disciplinary and Multi-objective Optimization Of Electmentioning
confidence: 99%
“…(i) Constructal entransy dissipation rate minimization with fixed magnetic field [159]. Based on the concept of entransy dissipation, the expression of the mean temperature difference with high thermal conductivity material inserted in the solenoid (electromagnet) was deduced.…”
Section: Multi-disciplinary and Multi-objective Optimization Of Electmentioning
confidence: 99%
“…Xie et al [56,57] optimized the heat transfer model of a rectangular solid wall with an open T-shaped cavity and with an open rectangular cavity with some constraints based on entransy dissipation rate minimization. A multidisciplinary optimization of electromagnet combing magnetic field and heat transfer was proposed by Wei et al [58] based on entransy dissipation rate minimization. The results of refs.…”
Section: Introductionmentioning
confidence: 99%
“…The results of refs. [55][56][57][58] showed that combing the extremum principle of entransy dissipation and heat transfer constructal theory could improve the heat transfer ability, but the results based on entransy dissipation rate minimization also showed that the assembling method proposed by Bejan could not decrease the entransy dissipation rate steadily as the assembling order increased.…”
Section: Introductionmentioning
confidence: 99%
“…Next, they used the entransy dissipation rate minimization as optimization objective and obtained the optimal construct using the constraint that new-order assembly must be assembled by the optimized last-order assembly [40]. Finally, Wei et al [41] derived the mean temperature difference for an electromagnet and made a multidisciplinary constructal optimization for electromagnets, which combined the magnetic density problem with the heat transfer problem. Based on the entransy dissipation rate minimization, Xie et al [42,43] optimized the heat generating bodies with rectangular cavity and T-shaped cavity.…”
mentioning
confidence: 99%